2016
DOI: 10.1017/orp.2016.1
|View full text |Cite
|
Sign up to set email alerts
|

Which Cognitive Biases can Exacerbate our Workload?

Abstract: Despite the advent of technologies that enhance productivity, the workload of many individuals, including psychologists, remains onerous, provoking burnout and similar complications. Although the circumstances that mitigate or exacerbate the effects of workload have been studied extensively, the antecedents of these demands have not been established definitively. Without this insight, managers cannot be sure of which practices are likely to contain the workload of individuals. To resolve this shortfall, we fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 103 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…The first step is to examine the workplace environment within public health administrative organisations to determine whether this may be exacerbating cognitive biases. Moss et al showed how a workplace environment that fostered a sense of meaning and purpose in people's lives could alleviate a number of cognitive biases [53]. Their particular focus was how these biases were related to burnout [53], which had been demonstrated in public administration, as well as in many other workplaces [54].…”
Section: The Way Forward: Research-informed Practicementioning
confidence: 99%
See 2 more Smart Citations
“…The first step is to examine the workplace environment within public health administrative organisations to determine whether this may be exacerbating cognitive biases. Moss et al showed how a workplace environment that fostered a sense of meaning and purpose in people's lives could alleviate a number of cognitive biases [53]. Their particular focus was how these biases were related to burnout [53], which had been demonstrated in public administration, as well as in many other workplaces [54].…”
Section: The Way Forward: Research-informed Practicementioning
confidence: 99%
“…Moss et al showed how a workplace environment that fostered a sense of meaning and purpose in people's lives could alleviate a number of cognitive biases [53]. Their particular focus was how these biases were related to burnout [53], which had been demonstrated in public administration, as well as in many other workplaces [54]. A workplace environment that could reduce a number of biases simultaneously could also improve the decision-making capability, which could then be related back to the central definition of policy capacity.…”
Section: The Way Forward: Research-informed Practicementioning
confidence: 99%
See 1 more Smart Citation
“…To conduct this review, we first identified existing taxonomies of biases from both consultation with researchers in decision making and literature searches. Three taxonomies were utilized (see Baron, 1994; Krueger and Funder, 2004; Moss et al , 2016).…”
Section: Identification Of Other Biasesmentioning
confidence: 99%